2011
DOI: 10.1186/1757-4749-3-10
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage-encoded shiga toxin gene in atypical bacterial host

Abstract: BackgroundContamination from fecal bacteria in recreational waters is a major health concern since bacteria capable of causing human disease can be found in animal feces. The Dog Beach area of Ocean Beach in San Diego, California is a beach prone to closures due to high levels of fecal indicator bacteria (FIB). A potential source of these FIB could be the canine feces left behind by owners who do not clean up after their pets. We tested this hypothesis by screening the DNA isolated from canine feces for the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Acquisition or enhancement of virulence traits is facilitated by the presence of environmental reservoirs of virulence genes. For example, metagenomics has revealed that a reservoir of exotoxin-encoding genes exists in the environment (5)(6)(7). As the temperature increases, there is increased stress on ecosystems such as coral reefs, and this stress makes organisms more susceptible to infectious disease.…”
Section: Global Climate Changementioning
confidence: 99%
See 1 more Smart Citation
“…Acquisition or enhancement of virulence traits is facilitated by the presence of environmental reservoirs of virulence genes. For example, metagenomics has revealed that a reservoir of exotoxin-encoding genes exists in the environment (5)(6)(7). As the temperature increases, there is increased stress on ecosystems such as coral reefs, and this stress makes organisms more susceptible to infectious disease.…”
Section: Global Climate Changementioning
confidence: 99%
“…Moreover, if these genes are found in alternative, noncognate environmental hosts, they serve as the genetic "raw material" for evolution of novel animal and human pathogens. As described below, the phage-encoded genes for Shiga toxin and staphylococcal enterotoxin A have been found in alternative hosts cultivated from environmental samples (5,6).…”
Section: Microbial Metagenomicsmentioning
confidence: 99%
“…In Western nations, beach water and sand quality monitoring has attracted significant attention in recent years owing to improved legislation (Casas et al, 2011). This development partly may be due to the availability of institutional frameworks-scientific, managerial and engineering competencies, considerable budgetary allocations and relevant political and stakeholder willpower that concertedly work to ensure the functionality of robust surveillance systems.…”
Section: Introductionmentioning
confidence: 99%
“…Yet in these countries, there have been accounts reported of alarming levels of bacteria found in faeces and dangerous heavy metals in contaminated storm water flowing into beaches (Oshiro and Fujioka, 1995;Olapade et al, 2006;Grant et al, 2001;Novais et al, 2005;Yoder et al, 2004;Debacker et al, 2000). This often results in a number of public health advisories and beach closures (Graham et al, 2009;Casas et al, 2011). Furthermore, epidemiological research on the effects on health of swimming at bathing beaches has shown that swimming in bathing beaches carries some risk of illness even when these beaches comply with existing legislative standards (Barrell et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The stx genes are carried by lambdoid phages, and these phages have disseminated stx genes among a wide variety of bacterial species, including E. coli (i.e., enterohemorrhagic E. coli [EHEC] and enteroaggregative hemorrhagic E. coli [EAHEC]) (10), Enterobacter cloacae (9,11), Escherichia albertii (12), and even Grampositive Enterococcus (13). EHEC, so named because it frequently causes hemorrhagic colitis (bloody diarrhea), often harbors one or several stx genes.…”
mentioning
confidence: 99%